Efficiency evaluation of selected Indian pharmaceutical firms since inception of product patent. (21st December 2020) - Bhattacharyya, Sucharita; Chatterjee, Susmita
The purpose is to measure the financial efficiency of selected Indian pharmaceutical firms in the product patent regime. The data envelopment analysis (DEA) technique for assessing the financial efficiency of pharmaceutical firms is used to fulfil the objectives of the study. DEA allows multiple inputs-outputs and we have applied an output-oriented the BCC model of the DEA technique which has allowed a breakdown of efficiency into technical and scale efficiency. In order to apply the DEA technique, secondary data has been collected from 63 large as well as medium/small Indian pharmaceutical companies. The results of statistical analysis are significant and reflect that the technical efficiency of the large pharmaceutical companies is higher than that of medium/small firms. Whereas the scale efficiency of medium/small companies is more than that of large companies. As medium/small firms have better scale efficiency the large firms should initiate control over their scale (size) of operation.